Superoxide Dismutase 1 Nanoparticles (Nano-SOD1) as a Potential Drug for the Treatment of Inflammatory Eye Diseases - Vaneev, Alexander N.; Kost, Olga A.; Eremeev, Nikolay L.; Beznos, Olga V.; Alova, Anna V.; Gorelkin, Peter V.; Erofeev, Alexander S.; Chesnokova, Natalia B.; Kabanov, Alexander V.; Klyachko, Natalia L. (Biomedicines, 2021)
Inflammatory eye diseases remain the most common clinical problem in ophthalmology. The secondary processes associated with inflammation, such as overproduction of reactive oxygen species (ROS) and exhaustion of the endogenous antioxidant system, frequently lead to tissue degeneration, vision blurring, and even blindness. Antioxidant enzymes, such as copper–zinc superoxide dismutase (SOD1), could serve as potent scavengers of ROS. However, their delivery into the eye compartments represents a major challenge due to the limited ocular penetration. This work presents a new therapeutic modality specifically formulated for the eye on the basis of multilayer polyion complex nanoparticles of SOD1 (Nano-SOD1), which is characterized by appropriate storage stability and pronounced therapeutic effect without side reactions such as eye irritation; acute, chronic, and reproductive toxicity; allergenicity; immunogenicity; mutagenicity even at high doses. The ability of Nano-SOD1 to reduce inflammatory processes in the eye was examined in vivo in rabbits with a model immunogenic uveitis—the inflammation of the inner vascular tract of the eye. It was shown during preclinical studies that topical instillations of Nano-SOD1 were much more effective compared to the free enzyme in decreasing uveitis manifestations. In particular, we noted statistically significant differences in such inflammatory signs in the eye as corneal and conjunctival edema, iris hyperemia, and fibrin clots. Moreover, Nano-SOD1 penetrates into interior eye structures more effectively than SOD itself and retains enzyme activity in the eye for a much longer period of time, decreasing inflammation and restoring antioxidant activity in the eye. Thus, the presented Nano-SOD1 can be considered as a potentially useful therapeutic agent for the treatment of ocular inflammatory disorders.